Analysis of the effectiveness of the use of financial resources in the procurement of pharmaceuticals for state needs - Malaev, M. G. (Kachestvennai͡a︡ klinicheskai͡a︡ praktika, 2022)
The use of different methods for analyzing the procurement of drugs for state needs made it possible to reveal the excessive range of drugs included in state contracts, as well as the low efficiency of the use of funds.